Advancing Environmental Sustainability: Integrating ESG Strategies in the Global Mobility and Relocation Industry - Eschrich, Matthew (Digital Repository of Theses, 2024)
The Relocation and Global Mobility industry was formed in 1969 as a catalyst to support enterprise mobility solutions for human capital deployment globally. As our world has continued to become increasingly globalized, it is imperative for the industry to evaluate current practices as it relates to environmental protection, as part of a holistic approach to preserving the environment for future generations. The Global Mobility industry market size is expected to reach $28.35bn by the year 2030, of which $17.66bn will originate from the United States. The United States has also historically seen that on average, 1.6%+ of eligible workers have relocated for a new job annually (Coherent Market Insights 2023). The industry has prioritized components of ESG, focusing primarily on the Social and Governance pieces. However, it has often overlooked the Environmental adoption. The industry produces substantial greenhouse gas emissions due to the procurement of relocation services for corporate mobility programs. This research project focuses on discovering the link between corporate mobility programs and their necessary coexistence within a sustainable framework which is critical for the future. It will evaluate whether environmental adoption within the industry is feasible for long-term growth while prioritizing people, the planet, and profits.